A Meta-analysis of the Effect of Probiotic Lactobacillus sp. as Immunomodulating Inflammatory Responses - Waode Fifin ERVINA; Sri Pantja MADYAWATI; Iswinarno Doso SAPUTRO; Dodi SAFARI; Rury Eryna PUTRI; Salma ZULQAIDA (Medeniyet Medical Journal)
Lactobacillus sp. is considered an indispensable probiotic, and this probiotic has an effective role in maintaining the immune system. We evaluated the effect of the probiotic Lactobacillus sp. on modulating inflammation in several cases. In collecting the literature, we used databases from the Web of Science, the Cochrane Central Register of Controlled Trials, PubMed, and Embase. Studies that met the inclusion criteria were analyzed using Review Manager (version 5.4). A p-value of <0.05 of the total effect is considered statistically significant. Finally, 1895 references were retrieved and 20 were included in the meta-analysis. This meta-analysis suggested that most cases in this study were healthy elderly who received treatment with Lactobacillus sp. Lactobacillus sp. has a positive effect on B cells, eosinophils, IgE, NK cells, TNF-α, and IL-10. Lactobacillus could regulate the immune system by modulating inflammation in the healthy elderly.